Focusing strategies of condom use against HIV in different behavioural settings: an evaluation based on a simulation model - van Vliet Carina; Meester Elisabeth I.; Korenromp Eline L.; Singer Burton; Bakker Roel; Habbema J. Dik F. (The World Health Organization, 2001)
Using a sexually transmitted diseases simulation model (STDSIM), we made projections of HIV spread for four profiles of sexual behaviour reflecting patterns encountered across the developing world: 1) much commercial sex, no short relationships; 2) commercial sex, concurrent short relationships; 3) concurrent relationships, no commercial sex; 4) serial short relationships, some commercial sex. We studied the effects of increasing condom use in three target groups: commercial sex workers (CSWs); men engaging in commercial contacts and short relationships; and females in steady relationships. The projections indicated that the CSW and male strategies were more effective in reducing HIV incidence than the strategy focusing on females in steady relationships. In the long run, even the group of men and women with one recent partner were better protected against HIV infection by condom use in high-risk contacts than by condom use in steady relationships. Furthermore, the numbers of HIV cases prevented per condom used were 7 to 500 times higher for condoms used by CSWs or men engaging in short relationships and commercial sex than for ones used by females in steady relationships. The results indicated the merit of focusing on high-risk groups irrespective of the pattern of sexual behaviour, even in epidemics that had already spread throughout populations.